Roadmap for cardiovascular circulation model. (29th September 2016) - Safaei, Soroush; Bradley, Christopher P.; Suresh, Vinod; Mithraratne, Kumar; Muller, Alexandre; Ho, Harvey; Ladd, David; Hellevik, Leif R.; Omholt, Stig W.; Chase, J. Geoffrey; Müller, Lucas O.; Watanabe, Sansuke M.; et al.
Abstract : Abstract: Computational models of many aspects of the mammalian cardiovascular circulation have been developed. Indeed, along with orthopaedics, this area of physiology is one that has attracted much interest from engineers, presumably because the equations governing blood flow in the vascular system are well understood and can be solved with well‐established numerical techniques. Unfortunately, there have been only a few attempts to create a comprehensive public domain resource for cardiovascular researchers. In this paper we propose a roadmap for developing an open source cardiovascular circulation model. The model should be registered to the musculo‐skeletal system. The computational infrastructure for the cardiovascular model should provide for near real‐time computation of blood flow and pressure in all parts of the body. The model should deal with vascular beds in all tissues, and the computational infrastructure for the model should provide links into CellML models of cell function and tissue function. In this work we review the literature associated with 1D blood flow modelling in the cardiovascular system, discuss model encoding standards, software and a model repository. We then describe the coordinate systems used to define the vascular geometry, derive the equations and discuss the implementation of these coupled equations in the open source computational software OpenCMISS. Finally, some preliminary results are presented and plans outlined for the next steps in the development of the model, the computational software and the graphical user interface for accessing the model.